(3HMhK GdYedjGJ aj GdeMGSHI (B/s - (3OHjGf, GdSjO YHO GdebUhOs; (3CHh RjO, ceGd NdjaI s; (3YHO GddWja, fGUQ fhQ GdOjf s ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2001)
(3feGPL GdHQeLI GdNWjI Jchjf GdfehPL hNWhGJ Md GdfehPL, JMdjd h GSJNOGe GdfJGFL(B-(3aMU hJbUj EfMQGaGJ GdJcGdja(B-(3fehPL JMdjd hGSJNOGe GdfJGFL(B-(3fehPL JMdjd GdeSJNOe GdefJL(B-(3JNWjW hQbGHI GdJcGdja HESJNOGe GdJMdjd GdTHcj(B-(3feGPL GdeMGcGI(B-(3feGPL GdHQeLI GdYOOjI GdUMjMIs
Keywords: (3GdHQeLIs; (3GdeMGSHIs; (3HMhK GdYedjGJs